Avalanche speed in thin avalanche photodiodes - Ong, D. S.; Rees, G. J.; David, J. P. R. (2003)
The duration of the avalanche multiplication process in thin GaAs avalanche photodiodes is investigated using a full band Monte Carlo (FBMC) model. The results are compared with those of a simple random path length (RPL) model which makes the conventional assumptions of a displaced exponential for the ionization path length probability distribution function and that carriers always travel at their saturated drift velocities. We find that the avalanche duration calculated by the RPL model is almost twice of that predicted by the FBMC model, although the constant drift velocities used in the former model are estimated using the latter. The faster response predicted by FBMC model arises partly from the reduced dead space but mainly from the velocity overshoot of ionizing carriers. While the feedback multiplication processes forced by the effects of dead space extend the avalanche duration in short structures, the effects of velocity overshoot in the realistic model more than compensate, significantly improving multiplication bandwidth. (C) 2003 American Institute of Physics.